2017
DOI: 10.1016/j.joca.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body vibration of mice induces progressive degeneration of intervertebral discs associated with increased expression of Il-1β and multiple matrix degrading enzymes

Abstract: Progressive IVD degeneration induced by WBV was associated with increased expression of Il-1β within the IVD that preceded Mmp and Adamts gene induction. Moreover, WBV-induced IVD degeneration is not reversed following cessation of vibration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 53 publications
(58 reference statements)
2
28
1
Order By: Relevance
“…Similarly, four of five CD-1 mice exposed to WBV for 4 weeks showed meniscal damage, and two of five showed focal damage to the articular cartilage associated with increased MMP-mediated matrix degradation 10 . Subsequent studies from our group showed that WBV-induced damage to both the IVD and knee joint increased in severity when CD-1 mice were exposed to 8 weeks WBV 11,12 . In direct contrast, the current study demonstrates that exposure of C57BL/6 mice to those same parameters of WBV did not induce degeneration-associated changes in either the knee or IVD after 4 or 8 weeks of exposure.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, four of five CD-1 mice exposed to WBV for 4 weeks showed meniscal damage, and two of five showed focal damage to the articular cartilage associated with increased MMP-mediated matrix degradation 10 . Subsequent studies from our group showed that WBV-induced damage to both the IVD and knee joint increased in severity when CD-1 mice were exposed to 8 weeks WBV 11,12 . In direct contrast, the current study demonstrates that exposure of C57BL/6 mice to those same parameters of WBV did not induce degeneration-associated changes in either the knee or IVD after 4 or 8 weeks of exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Sections were imaged on a Leica DM1000 microscope, with Leica Application Suite (Leica Microsystems). To evaluate IVD degeneration, midsagittal sections were scored using the modified Thompson grading scheme to assess IVD health based on criteria specific to each tissue compartment (scores 1e4, where a lower score corresponds to a more healthy tissue), as previously reported 10,12 . Knee joint health was assessed using the murine Osteoarthritis Research Society International (OARSI) histopathological scale 13 .…”
Section: Histological Analysesmentioning
confidence: 99%
“…Twenty-four hours after the final exposure to WBV, mice were euthanized by a lethal dose of sodium pentobarbital. Spinal tissues were isolated to characterize effects of WBV on the intervertebral disc and vertebral bone, detailed in 25 .…”
Section: Whole-body Vibrationmentioning
confidence: 99%
“…Targeting certain lncRNA give a new hope to IDD regeneration. ECM degrading enzymes ADAMTS5 serves as a promoter in IDD development [96,97]. A newly reported LncRNA named linc-ADAMTS5 is transcribed in the opposite direction to ADAMTS5.…”
Section: The Role Of Lncrnas In Cartilage Regenerationmentioning
confidence: 99%